Iowa RBA, November 20, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for November 20, 1995. Highlights of the update include sightings of an Iceland Gull, Black-legged Kittiwake, Red-throated Loon, Glaucous Gull, White-winged Scoter, Gyrfalcon, and a Prairie Falcon. Also included are handwritten notes for the next week's update with sightings of five Common Redpolls and several Pine Siskins. Epson - sheet feed/flatbed